AN ANALYSIS OF MATHEMATICAL REASONING ABILITY IN PROBLEM SOLVING WORD PROBLEM BASED ON GENDER AT UNIVERSITAS MUHAMMADIYAH LAMONGAN - Humairah Humairah (LP3M STKIP Muhammadiyah Muara Bungo, 2021)
This study aims to describe and analyze the mathematical reasoning and problem solving abilities of PGSD students, Universitas Muhammadiyah Lamongan, based on the gender in resolving story problems. This research is a qualitative descriptive research. The research subjects were 6 PGSD students of Universitas Muhammadiyah Lamongan who were selected based on the criteria of academic abilities; students with high reasoning, moderate reasoning, and low reasoning. The data collection techniques were observation, test, and interview. The data analysis was based on the results of test, observation, and interview obtained by students and based on table rubrics. Data analysis was carried out by the researcher using 6 subjects as representatives consisting of 3 males and 3 females with criteria previously mentioned (high, moderate, low). The results of data analysis on mathematical reasoning and problem solving abilities based on gender were female students' mathematical reasoning abilities were superior than male students' mathematical reasoning abilities. Keywords: Mathematical Reasoning, Problem Solving, Gender